Hubungan Peran Serta Orang Tua dengan Dampak Hospitalisasi pada Anak Usia Prasekolah di Ruang Al-Fajar RSUD Haji Makassar - Sriyanah, Nour; Efendi, Suradi; Nurleli, Nurleli; Mardati, Mardati (PT.Mantaya Idea Batara, 2021)
Hospital care is a new uncomfortable and stressful situation for children that is experienced by children due to many new pressures faced simultaneously. In this case, parents’ involvement and the importance of parents’ are essential to affect the healing process of children. This study aimed to recognize the relationships of parents’ roles with impact of hospitalization in preschoolers Al-Fajar room RSUD Haji Makassar 2017. This was analytical research with cross sectional study design in that number of sample was 31 preschool children in Al-Fajar room RSUD Makassar selected by accidental sampling. The results of this study were analyzed by using Chi-Square test that there was a relationship of parents’ participation with the impact of hospitalization of preschool age children in ? value = 0.001 value ? <0.05. It concluded that there was a relationship of parents’ role with the impact of hospitalization in preschool children. It is expected to parents to understand about the importance of parents’ participation in minimizing impact of hospitalization in preschool children and expected when children are exposed, parents should prepare themselves both physically and psychologically, therefore the role of parents can be applied well.